The Influence of Intensive Programs on The Achievement of Islamic Religious Education Achievement in MTs Al-Arif Gempol Pasuruan - Muna wir (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
It is common for every educational institution to implement teaching programs according to the curriculum set by the government in this case the Ministry of National Education or the Department of Religion. When examined carefully education is a determinant of the direction of one's life which is the smallest component of a society and nation. That's why MTs Al-Arif Gempol Pasuruan deems it necessary to improve the quality and quantity of Educators, Students and Students Facilities which are called Intensive Programs. Because there is no known influence between the intensive program and the learning achievement of Islamic religious education, the authors intend to conduct research with quantitative and qualitative approaches to test hypotheses.This intensive program is an effort to improve student learning achievement by handling more education factors through competent teacher qualifications, selecting raw student input, adding curriculum or materials, fulfilling learning facilities and infrastructure and increasing learning time. Thus it is hoped that the elevation of student learning achievement will be better.From the research we have done, intensive programs affect the learning achievement of Islamic religious education, this is evidenced by the results of statistical analysis obtained sufficient or moderate correlation with the calculation of the final value of rxy = 0.525 this case if connoted by the interpretation table is at the number 0,400 - 0,700 which has a moderate or moderate meaning.Considering that there are still deficiencies that need to be addressed in this intensive program, including not yet maximizing teacher qualifications, some students who lack discipline, unequal mastery of the material and lack of learning facilities and infrastructure. Then the collaboration of the school, parents, and students needs to be improved.Keywords: Intensive Program, Learning Achievement